Street Trading Activities in Kuala Lumpur’s Chinatown: Present Situation and Future Directions - Tan, Angelyn ‘G’-Ling; A Aminuddin, Asrul; Daud, Nila Inangda (MAJ - Malaysia Architectural Journal, 2020)
This research aims to understand the role of street trading activities in Chinatown and to promote its role in enhancing the livability of Kuala Lumpur in line with the government’s efforts to establish cultural and ethnic enclaves in the city. The objectives of this research are to identify the present situation of street trading activities and to investigate the informal use of streets and outdoor spaces as the setting for these businesses. The two findings of the study are firstly, the identification of the profile of street trading activities which includes the activity type, demographic profile of the traders and background of the business establishments. Secondly is the behavioural pattern and usage of the informal spaces, including the location, premise type and changes of the streetscape according to time. The paper serves to provide further directions in terms of urban planning and further site intervention that would be able to prevent the further loss of identity and dilution of the Chinese heritage in Kuala Lumpur. Chinatown holds a dear presence in the lives of the people,